Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content:1. The Impact of Friendship in Workplace on Job Commitment: A Field Study in Private Sector Automotive Companies in Saudi ArabiaMr. Ahmed Farouk A. Mohammed2. Financial Management: Foundations and Contemporary ChallengesMs. Ruwaida Saeed Alshehri3. The role of self-financing in achieving financial independence and academic quality in government higher education institutions in the Sultanate of Oman: An analytical study of challenges and opportunitiesMs. Noora Ahmed Al-Busaidi, Dr. Hafida Nia4. The Extent of the Affection of Some Factors on the Responsibility of External Auditor for Detection and Reporting Fraud Operations: An Empirical Study in the Kingdom of Saudi ArabiaMs. Bdour Saeed Alrefai5. Challenges of Using Artificial Intelligence in Human Capital Management at the Communications, Space, and Technology Commission in the Kingdom of Saudi ArabiaDr. Ahlam Melfi Alotaibi6. Marketing is a Positive Force in Contemporary Society: Case of Holland & Barrette Social CampaignMs. Ohoud Mohammed Algarni7. Holland & Barrett Health and Wellbeing Retailers Social Marketing Campaign: Case of Saudi Arabia ImplementationMs. Ohoud Mohammed Algarni
Keywords: Journal of Economic, Administrative and Legal Sciences